Information Society A Study of Related Theories and Technological and Economical Basics - Al Assafin, Issa (Latakia University Journal - Arts and Humanities Sciences Series, 2017)
The current study handles what related to the Information Society including aspects of concept, origin, essential terms that have been circulating on this concern, characteristics, in addition to the most significant theories of information society that have hypnotized the scholars of various backgrounds and specialties the most obvious of which are the sociologists, economists, and the technologists, not to mention the economical and technological essentials and their impact on such a society. This study concludes with a constellation of findings most important of which are: information become among the basic sources that obviously affect various sectors of life: economical, social and cultural. They are however looked at as a resource that could be utilized as a commodity. The improvements in the field of information technology has led to dividing societies into three constituents, as follows: sharing societies, affiliated societies and secluded societies.